2021
DOI: 10.1051/0004-6361/202140935
|View full text |Cite
|
Sign up to set email alerts
|

The Gaia-ESO survey: Mixing processes in low-mass stars traced by lithium abundance in cluster and field stars

Abstract: Aims. We aim to constrain the mixing processes in low-mass stars by investigating the behaviour of the Li surface abundance after the main sequence. We take advantage of the data from the sixth internal data release of Gaia-ESO, IDR6, and from the Gaia Early Data Release 3, EDR3s. Methods. We selected a sample of main-sequence, sub-giant, and giant stars in which the Li abundance is measured by the Gaia-ESO survey. These stars belong to 57 open clusters with ages from 130 Myr to about 7 Gyr and to Milky Way fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 135 publications
0
12
0
Order By: Relevance
“…Lagarde et al 2015), most authors have assumed that all of the observed extra mixing can be attributed to the thermohaline instability (e.g. Kirby et al 2016;Charbonnel et al 2020;Magrini et al 2021b). However, this connection has also been questioned for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Lagarde et al 2015), most authors have assumed that all of the observed extra mixing can be attributed to the thermohaline instability (e.g. Kirby et al 2016;Charbonnel et al 2020;Magrini et al 2021b). However, this connection has also been questioned for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…We place upper limits on the other three. However, while the Li content of NGC 2682 has been extensively studied in the literature (see e.g., Pace et al 2012;Carlos et al 2020;Magrini et al 2021a), there are no reported Li measurements for any of these stars, nor for stars of very similar atmospheric parameters. Therefore, a direct comparison is not meaningful.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…In any case, the spectra of field stars may be useful as a legacy, especially now that their distance is known thanks to the Gaia satellite results, see e.g. Magrini et al (2021) and Romano et al (2021), where field stars observed in the same field as the targeted OC were used to study the lithium distribution and evolution in giant stars.…”
Section: Targets Observed In the Different Kind Of Clustersmentioning
confidence: 99%